Control and Application of Terrain Curvature on Dynamic Disasters: A Case Study of Coal and Gas Outbursts in the Pingdingshan Mining Area, China. (12th June 2021) - Sun, Dequan; Chen, Ying; Li, Xiaoyan; Huang, Chunhui; Su, Huairui; Chen, Rujiao
Abstract : Based on coal and gas outburst mining area topography, a risk evaluation index for mine dynamic disasters in relation to terrain curvature is presented by analyzing the terrain curvature formation and determining its classification and computational methods. Clarifying the mechanism that the terrain curvature changes reflects the intensity of tectonic activity and the tectonic stress field variation, as well as coal and rock mass energy storing. By using the N-shaped landform in the Pingdingshan coal mine as a case study, an area having strong tectonic activity and coal and gas outbursts was recorded to occur where terrain curvature changed, notably occurring where the positive curvature radius was 80.21% of the total. These findings indicate that terrain curvature has significant controlling effects on coal and gas outbursts. A preliminary assessment for the occurrence risk of coal and gas outbursts using the terrain curvature value is proposed which can be used as an effective method to predict future outbursts.